The Influence of Adaptive Capability and Information Technology Capability Through Innovation as An Intervening Variable (Study on Traditional Riau Food SME’s in Pekanbaru) - Ami Arimbi; Samsir; Prima Andreas Siregar; Rio J.M. Marpaung (urn:multiple://2988-7828multiple.v3i24)
This study aims to determine the effect of adaptive capabilities and information technology capabilities on business performance through innovation as an intervening variable in Riau specialty food SMEs in Pekanbaru. The population in this study were typical Riau food MSMEs in Pekanbaru. The sampling technique used in this research is snowball sampling, namely the data collection technique which starts with a small number of data sources, but as the process progresses, the number increases, and the number of samples is determined by the Lemeshow formula, namely 100 typical Riau food SMEs. The analysis method used in this research is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach which is processed using SmartPLS software version 4.1.0.9. The results of research with hypothesis testing show that innovation has a positive and significant effect on business performance. Adaptive capability has a positive and significant effect on business performance. Information technology capability has a positive and significant effect on business performance. Information technology capabilities have a positive and significant effect on innovation. Innovation mediates the influence between adaptive capabilities on business performance. Innovation mediates the influence between information technology capabilities on business performance.